Doing time in the sociology of education. Issue 1 (2nd January 2017) - Lingard, Bob; Thompson, Greg
Abstract: This article is both an editorial introduction for this special issue and a distinctive contribution in its own right. The article seeks to extend a dynamic and multiple conception of time to the sociology of education to think beyond the clock time associated with modernity and industrialisation. This need is illustrated through an account and critique of E.P. Thompson's canonical account of clock time. The article argues that this construction of clock time implicitly frames most work in the sociology of education. The concept of 'timespace' offers a way to go beyond both clock time and the current 'spatial turn' in the sociology of education that prioritises space over time. It is shown how computerisation also ushers in a new temporality, which works simultaneously with clock time and perhaps presages the move from a disciplinary to control society. The article accepts that there are multiple and dynamic temporalities and correlatively supports a working together of historical and sociological imaginations towards a sociology of education that acknowledges and works with multiple temporalities, empirically, methodologically, theoretically and in research writing.